Discontinuation of Prosecution Theft Crime Through Humanist Restorative Justice House in Islamic Criminal Law in Lampung - Fatonah, Rini; Daffa Ladro Kusworo (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
The existence of restorative justice certainly brings a new paradigm in the settlement of criminal cases, by seeking to settle cases solely outside the court. The implementation of restorative justice-based termination of prosecution can be applied to the crime of theft as the highest number of cases in Indonesia. Meanwhile, there has recently been the establishment of restorative justice houses in each jurisdiction of the prosecutor's office to optimize the resolution of all legal problems by filtering cases that go to court, dissemination of law to residents, and being able to develop local wisdom by involving local traditional leaders to emphasize consensus deliberation. In essence, Islamic law is a modern law because it has recognized the form of restorative justice settlement in jarimah qisas and diyat. The concept of restorative justice in Islamic criminal law is carried out through peace and forgiveness by realizing the creation of justice and balance for the perpetrators of criminal acts and the victims themselves. The research approach is to use a normative juridical method with reference to laws and regulations sourced from primary data and literature studies originating from criminal law literature in Indonesia, which is then processed into a specific conclusion. The results of the study show that humanist restorative justice houses are an alternative to solving cases of theft. the embodiment of restorative justice in a hybrid way within the prosecutor's office will be achieved as a humane law enforcement agency in Lampung province. Forgiveness given by the victim, or his family can cancel the kisas punishment. Through the concept of diyat, compensation for compensation for the consequences of the crime can be felt directly by the victim or his family